Pengaruh Budaya Religius terhadap Kecerdasan Spiritual Peserta Didik Kelas Atas MI Nurul Huda Margorejo - Siti Nurjanah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to find out the influence of religious culture on the spiritual intelligence of learners. This research uses survey research methods. The population in this study was all 4th and 5th grade students of MI Nurul Huda Margorejo. The results showed that in analyzing religious culture at MI Nurul Huda Margorejo by using a test in the form of questionnaires and spiritual intelligence in the form of questionnaires, the calculation was carried out